Factors That Influence 3-Month Injectable Contraception with Increased Maternal Weight - Nursakiah (Cattleya Darmaya Fortuna, 2023)
Contraception is an effort to regulate child birth, ideal birth distance and age, and regulate pregnancy. Through promotion, protection and assistance in accordance with reproductive rights to quality (BKKBN). Developing countries such as Indonesia are active family planning users in Indonesia in 2018 with the number of couples of childbearing age ( PUS) who used family planning were 24,258. including the highest contraceptives are injection contraceptives, namely 15,261,014 (62.90%), second place are Pill contraceptives with 4,130,495 (17.02%), third place are IUD contraceptives with 1,759,862 (7.25%), fourth place is implants with 1,724,796 (7.11%), fifth place is MWO with 660,259 (2.72%), sixth place is condoms with 298,218 (1.22%) and lowest is MOP with 119,314 (0.49%) ) (Ministry of Health of the Republic of Indonesia, 2018). This type of research is an analytical survey with a cross sectional approach. The sampling technique used total sampling, namely that the entire population was sampled as many as 30 people. The data collection tool used was a questionnaire with 20 statements. The independent variables in this study are knowledge, age, education, employment and the dependent variable in this study is 3-month injectable contraception with an increase in maternal weight. Data processing is done by editing, coding, tabulating, then tested using the Chi-Squer test. For the knowledge variable Regarding weight gain for mothers, 5 respondents (16.7%) found good criteria, 20 respondents (66.7%) had adequate criteria and 5 respondents (16.7%) had poor criteria. From the research results, it was found that there was an influence of education and work on the increase in weight of Eastern mothers at the Midwife Novi Lintas clinic with a p-value of 0.021 < 0.05 and 0.036 < 0.05.